Introduction to multicultural counseling for helping professionals - Lee, Wanda M.L; Lee, Wanda M. L.; Orozco, Graciela L.; Blando, John A.; Shooshani, Bita (Routledge, 2014)
Introduction to Multicultural Counseling for Helping Professionals is a valuable addition to the field. Written from the perspective of multicultural competence, it is practical, accessible, and yet grounded in the literature which makes it an ideal textbook for trainees. While covering the critical issues in providing effective multicultural counseling to different sub-populations, it nevertheless touches upon key principles and insights